Odpowiedź :
Odpowiedź:
a) 3x + 10 - 2x = 4x + 1
3x - 2x - 4x = 1 - 10
-3x = -9
x = 3
spr:
3 * 3 + 10 - 2 * 3 = 4 * 3 + 1
9 + 10 - 6 = 12 + 1
13 = 13
b) 8 - 2x - 5 + 5x = 8 + 4x - 3
-2x + 5x - 4x = 8 - 3 + 5 - 8
-x = 2
x = -2
spr:
8 - 2 * (-2) - 5 + 5 * (-2) = 8 + 4 * (-2) - 3
8 + 4 - 5 - 10 = 8 - 8 - 3
-3 = -3
c) 7x - 4 + 3x + 6 = 9 - 2x + 7 + 5x
7x + 3x + 2x - 5x = 9 + 7 - 6 + 4
7x = 14
x = 2
spr:
7 * 2 - 4 + 3 * 2 + 6 = 9 - 2 * 2 + 7 + 5 * 2
14 - 4 + 6 + 6 = 9 - 4 + 7 + 10
22 = 22
d) 1 - 4x - 5 - 5x + 2 = 6x -6 - 8x - 3
-4x - 5x -6x + 8x = -6 -3 - 2 + 5 - 1
-7x = -7
x = 1
spr:
1 - 4 * 1 - 5 - 5*1 + 2 = 6 * 1 - 6 - 8*1 - 3
1 - 4 - 5 - 5 + 2 = 6 - 6 - 8 - 3
-11 = -11
a) 8 + 5x + 2 = -3x + 7 + 2x
5x + 3x - 2x = 7 - 2 - 8
6x = -3
x = -0,5
spr:
8 + 5 * (-0,5) + 2 = -3 * -(0,5) + 7 + 2 * (-0,5)
8 - 2,5 + 2 = 1,5 + 7 -1
7,5 = 7,5
b) 3x - 4 + 2x = 7x - 5 + x
3x + 2x - 7x - x = -5 + 4
-3x = 1
[tex]x=\frac{1}{3}[/tex]
spr:
[tex]3*\frac{1}{3}-4+2*\frac{1}{3}=7*\frac{1}{3}-5+\frac{1}{3}[/tex]
[tex]1 - 4 + \frac{2}{3} = 2\frac{1}{3}-5 + \frac{1}{3}[/tex]
[tex]-2\frac{1}{3} = -2\frac{1}{3}[/tex]